Enhancements of pinning by superconducting nanoarrays - Navarro, E.; Monton, C.; Pereiro, J.; Basaran, Ali C.; Schuller, Ivan K. (Amer Physical Soc, 2015)
We present a comparative study of vortex pinning efficiency in superconducting (V) thin films grown on two similar triangular arrays of superconducting (Nb) and nonsuperconducting (Cu) nanodots. Resistance and magnetization anomalies at the same matching fields confirm the same pinning periodicity in both samples. However, we found two distinct features: First, the sample with superconducting dots shows stronger pinning that appears as sharper matching peaks in magnetization loops and shows higher critical current density and larger critical field at low temperatures. Second, an overall increase in the resistance of the V film with Nb nanodots is observed, while there is a crossover in the temperature dependence of the critical field and the critical current of both samples at T = 3K. This crossover corresponds to the temperature when the superconducting coherence length of V thin film equals the edge-to-edge distance between nanodots. We argue that this change in superconducting properties is related to the change in the superconducting regime from pinning enhancement at low temperatures to a superconducting wire network at high temperatures.
Keywords: Antidot Lattice; Magnetic-Field; Wire Networks; Arrays; Films; Dots; Transition; Size